Thermal Tolerance and Temperature‐Dependent Feeding Behavior of F1 Gulf and Atlantic Coast Striped Bass Strains. (20th February 2022) - Kenter, Linas W.; Berlinsky, David L.
Abstract: To evaluate the pond culture potential of purebred Striped Bass Morone saxatilis, the thermal stress tolerance and associated feeding behavior of Atlantic coast (Delaware River; DE) and Gulf of Mexico (Florida; FL) strains (~1.0–1.6 kg) were evaluated. In the first experiment, critical thermal maxima (CTmax) temperatures were determined by gradually increasing the water temperature of individual fish that were housed in 311‐L insulated containers (0.3°C/min) and determining when the fish experienced loss of equilibrium ( n  = 6/strain). The results indicated that the fish from the FL strain had a higher CTmax value (36.7 ± 0.32°C) than did those from the DE strain (35.7 ± 0.57°C). In the second experiment, feeding behavior and feed consumption were evaluated during simulated summer temperature fluctuations by increasing the water temperature from 26°C to 34°C by 2°C every 2 d ( n  = 30 fish/strain). Feed consumption decreased inversely with temperature in both strains until a mortality event occurred at 34°C. The results suggest that there are physiological adaptations to elevated temperatures among Striped Bass strains and they may be suitable for pond culture if feeding is restricted at high temperatures (>30°C).